A case study on occupational exposure to Chromium (VI), Nickel, PAH mixtures and lung cancer. - Silva, Maria João (2020)
Background: In several industries, e.g., aircrafts maintenance, workers are co-exposed to a range of hazardous substances, including hexavalent chromium [Cr (VI)], nickel (Ni) and polycyclic aromatic hydrocarbons (PAHs). Each of these compounds can cause serious health effects, including lung cancer. However, the association between exposure and health outcome has not been analysed from a mixture perspective, i.e., considering the potential interactive effects of those substances as determinants of lung cancer. Here we present the development of a case study on occupational exposure to Cr (VI), Ni and PAHs to advance the identification of mixture health effects and to progress towards a more refined risk assessment. Methods: A tiered framework is applied that includes a first step of collection of relevant hazard (e.g., genotoxicity) and exposure information gathered from literature or from HBM4EU databases on occupational cohorts. Then, this information will be used to construct hazard quotients derived from relevant occupational exposure limits for Cr (VI), Ni and PAHs, followed by the determination of the Hazard Index (HI). Results: The estimations based on available literature search will be presented and discussed, keeping the perspective of its contribution to generate directions for the exposure, hazard, and risk assessments. In addition, the biomonitoring levels of Cr (VI) and Ni and the data on external levels of PAHs produced in the chromate occupational exposure study, will allow a refinement of the exposure assessment, comparatively to the literature-based results obtained. Conclusions: It is anticipated that the assessment of the risk from occupational co-exposure to Cr(VI), Ni and PAHs - based on data obtained from a EU-wide harmonised study - will add on building a framework for mixtures risk assessment, that can be further applied for substances to which co-exposure occurs or/and are expected to produce similar health outcomes.